Userbase a user's guide on influencing mainstream media through online user-dominated video communities - Aquino, Jose Benigno A. 1989- (2012)
"This research explored the popularity of online video consumption and how user comments may have surfaced through grabs of mainstream media content uploaded by users of the website Youtube. It analyzed instances when these very users voiced their insights and criticisms of mainstream messages using the web video, and in case of the research how these users interpreted the issues that were brought up by the mainstream media involving the incident of the Manila Grandstand hostage incident. Simply put, this research is a descriptive study of how Youtube users use the service to effectively air their concerns and share these concerns with other users of the new media. It is evident that the users who commented on the video's comment threads were quite informed about the issues surrounding the hostage taking, and there are also indicators that suggest that these users actually involve themselves more in the discussions, going as far as talking about issues that for them are significant but not immediately related to the issue, i.e., issues involving government and police force budgets, conspiracy theories etc. Because of this, it can be theorized that the online video community--specifically the local Filipino community could actually use their online capability to better improve their knowledge of a certain issue and more effectively react to and perceive ideaas that they come across during their online interactions with different users. This leads the users to be more empowered in terms of their involvement not only in online interactions but as well as on matters of public interest."